PERAN MODAL SOSIAL TERHADAP TINGKAT KESEJAHTERAAN PELAKU INDUSTRI RUMAHAN (PENJAHIT BUSANA) DI KOTA MAKASAR - A. Nur Maida; St. Aisyah Hading; Hamida Suryani (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Micro-scale enterprises are one form of business venture to realize the level of community welfare in a non-formal environment. Home industry actors (fashion tailors) have their own ways of developing their businesses, for this reason this study aims to: 1. determine the transfer of knowledge obtained by home industry actors (fashion tailors) and 2. identify the role of social capital in the welfare level of home industry actors (fashion tailors) in Makassar City. The method in the research conducted was descriptive qualitative, namely with interview techniques, documentation, and questionnaires. The results of the research analysis show that 1. the transfer of knowledge obtained by home industry players (fashion tailors) in Makassar City in Parang tambung Village, Tamalate District is obtained from experience, knowledge and skills learned, attending training conducted by the Department of Labor and Cooperatives, courses and opportunities conducted by several free institutions, joining several tailoring communities and some of them continue the inheritance of parents' businesses that have been carried out, some open their own businesses with capital skills or loans based on education that is relevant to the field being run. And this industrial business is running well with promising profits. 2. the role of social capital on the welfare level of home industry actors (tailors).